Thyroid Function in Pregnant Women With Moderate to Severe Alcohol Consumption Is Related to Infant Developmental Outcomes - Donald, Kirsten A.; Wedderburn, Catherine J.; Barnett, Whitney; Hoffman, Nadia; Zar, Heather J.; Redei, Eva E.; Stein, Dan J. (Frontiers in Endocrinology, 2018)
Introduction: Fetal alcohol spectrum disorders (FASD) have an estimated global prevalence of 2-5% of births, but prevalence is reported to be as high as 15.5% for FASD in certain high-risk communities in South Africa. Preclinical studies demonstrate that alcohol consumption during pregnancy interferes with thyroid hormone availability and function and negatively impacts exposed offspring. Very little is currently reported on this phenomenon in humans. Methods: This pilot study was embedded in the Drakenstein Child Health Study, a multi-disciplinary longitudinal birth cohort study investigating the early biological and psychosocial determinants of child health in South Africa. 21 mothers and their children with moderate-severe prenatal alcohol exposure (PAE) and 19 mothers and their children with no alcohol exposure were investigated. Maternal exposure history and blood samples were collected in mid-pregnancy, and analyzed for serum free thyroxin (FT4), free triiodothyronine (FT3), and TSH. Children were assessed with formally measured growth parameters and development was evaluated using the Bayley III Scales of Infant and Toddler Development (BSID III) at 6 and 24 months of age. Results: While there were no significant differences in serum TSH and FT4 between groups, FT3 levels were significantly higher in mothers with moderate-severe prenatal alcohol use. In abstinent pregnant women, levels of FT4 were significantly correlated with infants’ scores on cognitive measures at 6 and 24 months of age and with levels of gross motor skills at 24 months. However, in mothers with alcohol use, FT4 levels were not correlated with any cognitive or motor skills, but FT3 levels were significantly associated with scores on children’s social-emotional development at 24 months of age. Discussion: Thyroid function in PAE is sufficiently disrupted to lead to alterations in serum FT3 levels. The contrast in findings between PAE and abstinent dyads in their association of maternal thyroid function and infant development further suggests that such disruption is present and may contribute to adverse neurodevelopment. Further work is needed to determine the relationship between peripheral thyroid indices during pregnancy and neurodevelopmental outcomes in the context of PAE.